Financial Management Training and Education Implementation in Elevating Low Income Family Empowerment - Noor, Agus Hasbi (Universitas Nusantara PGRI Kediri, 2024)
This research aims to explores the implementation of financial management training in empowering low-income families in Kabupaten Cianjur. Using a qualitative approach and a case study method, data was collected through in-depth interviews, observations, and document study. The informants in this research consists of a training manager, a training resource person, and 10 trainees. The findings provided a holistic view of the training's implementation and outcomes. Data analysis involved coding, theme identification, and interpretation to extract meaningful insights. The findings highlight the importance of expert involvement, tackling financial misconceptions, and the use of effective pedagogical strategies for comprehensive understanding. The positive reception from participants and observed behavioral shifts emphasize the tangible benefits of the training. The study concludes by emphasizing the critical role of financial education in fostering genuine, sustained financial empowerment among low-income populations.